Optimization of Cooling System Matching for EMU Auxiliary Power Unit - ZHANG Xiao; LIU Changqing; ZHOU Wenyong (Kongzhi Yu Xinxi Jishu)
Traditional converter design requires a large amount of experiments to verify whether the product meets the technical requirements and exists some problems like long design period, high cost, limited data and hard optimization. With numerical simulation, taking permanent magnet EMU auxiliary power converter as a research object, the cooling system was simulated and thus realized multi-objective optimization including temperature rise of electrical component, flow distribution, air duct structure, flow resistance and fan turbine selecting and matching. Test results verify that the simulation results have good accuracy and can realize first-time success of the design.